2018
DOI: 10.1177/0748730418797820
|View full text |Cite
|
Sign up to set email alerts
|

Implicating a Temperature-Dependent Clock in the Regulation of Torpor Bout Duration in Classic Hibernation

Abstract: Syrian hamsters may present 2 types of torpor when exposed to ambient temperatures in the winter season, from 8°C to 22°C (short photoperiod). The first is daily torpor, which is controlled by the master circadian clock of the body, located in the SCN. In this paper, we show that daily torpor bout duration is unchanged over the 8°C to 22°C temperature range, as predicted from the thermal compensation of circadian clocks. These findings contrast with the second type of torpor: multi-day torpor or classic hibern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…In many small hibernators, length of each torpor bout gradually increases from the beginning, reaches its peak in the middle, and then decreases at the end of the hibernation season, even in constant ambient temperature conditions (MacCannell & Staples, 2021) (Ortmann & Heldmaier, 2000) (Arnold et al, 2011) (Sheriff et al, 2013) (Siutz et al, 2018). Ambient and core body temperatures also affect duration of each deep torpor bout, suggesting involvement of a temperature-sensitive process in the regulation of torpor-IBA cycles (MacCannell & Staples, 2021) (Twente & Twente, 1965) (Geiser & Kenagy, 1988) (Malan et al, 2018). Metabolic rate measured by oxygen consumption contributes to the determination of torpor-IBA timings in golden mantled ground squirrels and garden dormice (Geiser & Kenagy, 1988) (Ruf et al, 2021), although the exact metabolic process responsible for determination of torpor-IBA timing is not yet clear.…”
Section: Discussionmentioning
confidence: 99%
“…In many small hibernators, length of each torpor bout gradually increases from the beginning, reaches its peak in the middle, and then decreases at the end of the hibernation season, even in constant ambient temperature conditions (MacCannell & Staples, 2021) (Ortmann & Heldmaier, 2000) (Arnold et al, 2011) (Sheriff et al, 2013) (Siutz et al, 2018). Ambient and core body temperatures also affect duration of each deep torpor bout, suggesting involvement of a temperature-sensitive process in the regulation of torpor-IBA cycles (MacCannell & Staples, 2021) (Twente & Twente, 1965) (Geiser & Kenagy, 1988) (Malan et al, 2018). Metabolic rate measured by oxygen consumption contributes to the determination of torpor-IBA timings in golden mantled ground squirrels and garden dormice (Geiser & Kenagy, 1988) (Ruf et al, 2021), although the exact metabolic process responsible for determination of torpor-IBA timing is not yet clear.…”
Section: Discussionmentioning
confidence: 99%
“…Ambient and core body temperatures also affect duration of each deep torpor bout, suggesting involvement of a temperature-sensitive process in the regulation of torpor-IBA cycles 13,[25][26][27] .…”
Section: Discussionmentioning
confidence: 99%
“…In many small hibernators, length of each torpor bout gradually increases from the beginning, reaches its peak in the middle, and then decreases at the end of the hibernation season, even in constant ambient temperature conditions (MacCannell & Staples, 2021) (Ortmann & Heldmaier, 2000) (Arnold et al, 2011) (Sheriff et al, 2013) (Siutz et al, 2018). Ambient and core body temperatures also affect duration of each deep torpor bout, suggesting involvement of a temperature-sensitive process in the regulation of torpor-IBA cycles (MacCannell & Staples, 2021) (Twente & Twente, 1965) (Geiser & Kenagy, 1988) (Malan et al, 2018). Metabolic rate measured by oxygen consumption contributes to the determination of torpor-IBA timings in golden mantled ground squirrels and garden dormice (Geiser & Kenagy, 1988) (Ruf et al, 2021), although the exact metabolic process responsible for determination of torpor-IBA timing is not yet clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in Syrian hamsters, the circadian system does not participate in the temporal organization of torpor–arousal cycles during prolonged hibernation at 6°C (Oklejewicz, Daan & Strijkstra, 2001). Recent research has revealed that a temperature‐dependent clock regulates the reduction of MR in multi‐day torpor and regains circadian synchronization after arousal (Malan et al ., 2018). In golden‐mantled ground squirrels ( Spermophilus lateralis ) and Arctic ground squirrels, the circadian clock genes and c‐fos expression in the SCN are suppressed during deep torpor and reversed during arousal from a torpid state (Bitting et al ., 1994; Ikeno et al ., 2017).…”
Section: The Central Neural Network Controlling Torpor‐related Physimentioning
confidence: 99%